Conflict cause analysis between stakeholders in a utility-scale PV plant and its policy improvement methods in Korea. (October 2018) - Kim, Ik-Pyo; Hwang, Ha Sung; Jung, Jin-Woo
Abstract: Despite the technological advances and the Korean government's ongoing efforts to expand the PV market, disputes related to the quality and performance of the utility-scale PV systems are not uncommon. Therefore, actual dispute cases in Korea are analysed to elicit their root causes and suggest effective remedies in this paper. This analysis focuses on the following three types of disputes caused by: (i) PV system installation quality, (ii) PV system performance degradation and (iii) natural disaster damage. Based on interviews and examination of the PV plants in dispute, it was drawn that conflicts between the stakeholders stem from limitations to utility-scale PV plants' evaluation and technical dispute management, lack of PV module reliability and lax contract terms for procurement. To mitigate the conflicts between domestic PV stakeholders, the following four policy improvements are suggested: improvements of PV plants' deployment procedure and quality assurance system that can detect failures of equipment in early stages, introduction of a government-led dispute settlement system, enforcement of strict quality standards for PV modules and provision of information on PV procurement specifications. The lessons and suggested remedies will help policy makers understand the domestic PV market and redesign the policies for mitigation of potential disputes. Highlights: Disputes pertaining to utility-scale PV system failures are not uncommon in Korea. Case studies show how disputes among stakeholders evolve in Korean PV market. Some PV dispute cases originate from insufficient national quality assurance system. This study suggests the dispute mitigation remedies for PV policy makers.